Work readiness and life goals among final-year students in Madiun - Caecilia Chyntia Ayuning; Marcella Mariska Aryono (Program Studi bimbingan Konseling PPs UNM Makassar, 2023)
This study aims to determine work readiness in terms of life goals owned by final year students in Madiun. This research is a quantitative study with a correlational approach. The population of this study were final year students studying at universities in Madiun City. Sampling using purposive sampling technique with a total of 172 final year students. The scales used were the work readiness scale and the life purpose scale, distributed online via google form. Correlation analysis using spearman's rho. The results of the spearman's rho correlation coefficient in this study showed insignificant results with sig (2-tailed) 0.647> 0.05 with a correlation score of 0.035. It means that the relationship between work readiness and life goals is very weak or insignificant. Based on the results of the study, it can be concluded that there is no relationship between work readiness and the life goals of final year students in Madiun. The recommendation of this study is to explore other variables that affect work readiness, such as self-efficacy and optimism with similar subject characteristics